Fiber of cotton plant cultivar under drought conditions - Lima, Antônia Samia; Costa, Maria Eugênia da; Cavalcanti, José Jaime Vasconcelos; Rodrigues, Ana Paula Medeiros dos Santos; Mendonça Júnior, Antonio Francisco de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
In order to evaluate the fiber characteristics of the different cotton cultivars, a research field was carried out in the Quixeramobim, Ceará, municipality, where the geographical coordinates Latitude (S ) 05 ° 11'57 ''S, Longitude (W) 39 ° 17'34''W and Altitude (M) 191. The local rainfall varies from 700 to 750 mm. These rains are concentrated in the period from January to June. The time of the Quixeramobim planting, was in February characterizing like normal crop. The experimental design was a randomized complete block design with four replications and twenty treatments. The experimental plot consisted of four linear 5-meter lines, spacing 0.90 meters between rows, 6 to 9 plants / m. The useful area of the plot used to obtain the data were the two central lines, in this test the strains and or cultivars were used referring to the year/crop 2019. It was concluded that there are phenotypic variability the treatments presented significant differences for the majority BRS 416, BRS 286 and BRS 293 are the best performance because they associated the best averages for feather productivity and fiber characteristics.